Prion proteins - Tatzelt, Jorg.; Apostol, M. I.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Genetics of Prion Disease, by S. Lloyd, S. Mead and J. Collinge.- Atypical Prion Diseases in Humans and Animals, by M. A. Tranulis, S. L. Benestad, T. Baron and H. Kretzschmar.- Chronic Wasting Disease, by S. Gilch, N. Chitoor, Y. Taguchi, M. Stuart, J. E. Jewell and H. M. Schätzl.- Transgenic Mouse Models and Prion Strains, by G. C. Telling.- Neuroprotective and Neurotoxic Signaling by the Prion Protein, by U. K. Resenberger, K. F. Winklhofer and J. Tatzelt.- Prion Seeded Conversion and Amplification Assays, by C. D. Orrú and B. Caughey.- Prion Protein and Its Conformational Conversion: A Structural Perspective, by W. K. Surewicz and M. I. Apostol.- Molecular Dynamics as an Approach to Study Prion Protein Misfolding and the Effect of Pathogenic Mutations, by M.W. van der Kamp and V. Daggett.- Chemical Biology of Prion Protein: Tools to Bridge the In Vitro/Vivo Interface, by R. Seidel and M. Engelhard.- The PrP-Like Proteins Shadoo and Doppel, by D. Westaway, N. Daude, S. Wohlgemuth and P. Harrison.- Fungal Prions: Structure, Function and Propagation, by M. F. Tuite, R. Marchante and V. Kushnirov.
Genetics of Prion Disease, by S. Lloyd, S. Mead and J. Collinge -- Atypical Prion Diseases in Humans and Animals, by M. A. Tranulis, S. L. Benestad, T. Baron and H. Kretzschmar -- Chronic Wasting Disease, by S. Gilch, N. Chitoor, Y. Taguchi, M. Stuart, J. E. Jewell and H. M. Schätzl -- Transgenic Mouse Models and Prion Strains, by G. C. Telling -- Neuroprotective and Neurotoxic Signaling by the Prion Protein, by U. K. Resenberger, K. F. Winklhofer and J. Tatzelt -- Prion Seeded Conversion and Amplification Assays, by C. D. Orrú and B. Caughey -- Prion Protein and Its Conformational Conversion: A Structural Perspective, by W. K. Surewicz and M. I. Apostol -- Molecular Dynamics as an Approach to Study Prion Protein Misfolding and the Effect of Pathogenic Mutations, by M.W. van der Kamp and V. Daggett -- Chemical Biology of Prion Protein: Tools to Bridge the In Vitro/Vivo Interface, by R. Seidel and M. Engelhard -- The PrP-Like Proteins Shadoo and Doppel, by D. Westaway, N. Daude, S. Wohlgemuth and P. Harrison -- Fungal Prions: Structure, Function and Propagation, by M. F. Tuite, R. Marchante and V. Kushnirov.
Electronic reproduction.
Keywords: Prions; Electronic books